STRATEGI PEMERINTAH INDONESIA UNTUK MENINGKATKAN DAYA SAING COFFEE LUWAK DALAM PASAR GLOBAL - ", Yutika; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Kopi Luwak (Luwak Coffee) is one of the original in the internal affairs of Indonesia (natural given). Luwak Coffee is coffee indigenous diracik coffee bean derived from a group that has been chosen selectively and consumed by Luwak (paradox harmaproditus) or better known as asian palm civet. The purpose of this research is to know strategy The Government of Indonesia to improve competitive luwak coffee in global market and the factors that affect strategy the government of Indonesia to increase competition in the global market luwak coffee.The data collected by using technical research library research (literature), data internet, and interview technique source. The three used as the effort to get more valid research results, with the process data can complement each other and to each other, so that researchers also can be understood to these issues, and have a certain satisfaction.Internationally, Indonesia as a country coffee producers to 3 in the world after Brazil and Vietnam plays a vital roles in the global market. These factors that affect competitiveness luwak coffee, one of them: Kopi luwak as cruelties animals, could not guarantee that There is a competitor Coffee Luwak.Keyword : Strategy, The Government of Indonesia , global market, Luwak Coffee